Nucleos(t)ide analogs continuation is not associated with a lower risk of HBsAg seroreversion following PEG-IFN-induced HBsAg loss - Na Gao; Haishi Wu; Bin Li; Huiying Yu; Lili Wu; Jing Zhang; Nan Zhang; Bingliang Lin; Qiyi Zhao; Zhiliang Gao (Virology Journal)
Abstract Background/Aims It is unclear whether nucleos(t)ide analogs (NUCs) continuation provides clinical benefits following HBsAg seroclearance with pegylated interferon (PEG-IFN)-based therapy. This study aims to investigate the role of NUCs continuation in HBsAg seroreversion. Methods Patients who experienced serum HBsAg loss after PEG-IFN-based therapy were enrolled and followed up for 96 weeks. Propensity score matching (PSM) was performed using a 1:1 ratio to adjust for the associated factors. A multivariate logistic regression analysis was used to determine the factors associated with HBsAg seroreversion. Results In total, 220 patients with HBsAg seroclearance were divided into NUCs (n = 54) and non-NUCs (n = 166) consolidation therapy groups. At week 96, the HBsAg seroreversion (12/54 vs. 31/166, P = 0.709) and virological relapse (2/54 vs. 10/166, P = 0.759) rates were similar in the NUCs and non-NUCs groups. After PSM, HBsAg seroreversion (12/53 vs. 13/53; P = 1.000) and virological relapse (2/53 vs. 4/53; P = 0.674) rates were not significantly different between the two groups. Serum hepatitis B surface antibody titer (odds ratio, 0.388; 95% confidence interval, 0.245–0.616; P < 0.001) was found to be associated with HBsAg seroreversion, while NUCs continuation was not related to HBsAg seroreversion. Conclusions NUCs continuation is not associated with a lower risk of HBsAg seroreversion in patients with serum HBsAg loss following PEG-IFN-based therapy.